Pengaruh Penggunaan Metronom Terhadap Stabilitas Tempo Dalam Menyanyikan Lagu Ibu Kita Kartini pada Ekstrakurikuler di SMA Negeri 1 Belitang - Wicaksana, Agung Amanda; Sepdwiko, Deria; Hera, Treny (Institut Teknologi Pendidikan Indonesia, 2023)
This study aims to determine the effect of the metronome on tempo stability when students sing Ibu Kita Kartini's song. to approach this problem, the Jack Plano theory is used, namely, stability is stability, balance stability, and consistency that affect singing Ibu Kita Kartini's song. the research method used is quantitative. the data was collected through a questionnaire, pre-test, and post-test. The data analysis technique used is the normality test and the hypothesis t-test. this study concludes that there is an effect of using the metronome on the stability of the tempo of extracurricular students with the final average score of 72 which is in the right category in the stability of the tempo of singing Ibu Kita Kartini.